The association of maternal Vitamin D status with infant birth outcomes, postnatal growth and adiposity in the first 2 years of life in a multi-ethnic Asian population: The Growing Up in Singapore Towards healthy Outcomes (GUSTO) cohort study - Ong, Yilin (Cambridge University Press, 2016)
10.1017/S0007114516000623